EKSISTENSI JAMU SEBAGAI WARISANWARISAN GASTRONOMI DI ERA MODERN KOTA YOGYAKARTA - Jessica Olive Limanto; Vishnuvardhana S. Soeprapto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia is an archipelagic country that was rich in traditions and local wisdom, one of which is jamu, a traditional Indonesian herbal beverage that was recognized by UNESCO as an Intangible Cultural Heritage of Humanity in 2023. In the modern era, the existence of jamu faces challenges due to changing lifestyles, particularly among younger generations who tend to prefer instant and ready-to-drink beverages over traditional herbal drinks. This condition highlights the need for preservation and adaptation efforts to ensure that jamu remains relevant amid contemporary developments. This study aims to examine the existence of traditional jamu in Yogyakarta City from a gastronomic perspective by analyzing its history, traditions, philosophy, raw materials, production processes, and methods of presentation, as well as understanding the role of various stakeholders in sustaining jamu culture. The study employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The analysis is based on Dewi Turgarini’s gastronomic framework and the seven indicators of cultural sustainability proposed by Soini & Birkeland, (2014), namely cultural heritage, vitality, diversity, locality, economic viability, eco-cultural civilization, and eco-cultural resilience. Research subjects were identified using the Nona Helix framework, which encompasses nine stakeholder groups involved in the preservation and development of jamu gastronomy. The findings indicate that traditional jamu in Yogyakarta continues to exist and adapt through product innovation, modern packaging, social media utilization, and digital marketing while maintaining its traditional values, health philosophy, and use of natural ingredients as its core identity. The sustainability of jamu largely depends on the preservation of intergenerational knowledge, community participation, continuous innovation, and the support of multiple stakeholders within the broader gastronomic ecosystem.